Uncoupling proteins in human heart. - Murray, A; Anderson, R; Watson, G; Radda, G; Clarke, K (2004)
Abnormal energetic activity in heart failure correlates inversely with plasma free-fatty-acid concentrations. However, the link between energetic and metabolic abnormalities is unknown. To investigate this association, we obtained blood samples from 39 patients undergoing coronary artery bypass graft surgery. Patients fasted overnight before samples were taken. When plasma free-fatty-acid concentrations were raised, cardiac mitochondrial uncoupling proteins (UCP) increased (isoform UCP2, p<0.0001; isoform UCP3, p=0.0036) and those of glucose transporter (GLUT4) protein decreased (cardiac, p=0.0001; skeletal muscle, p=0.0006). Consequently, energy deficiency in heart failure might result from increased mitochondrial UCPs (ie, less efficient ATP synthesis) and depleted GLUT4 (ie, reduced glucose uptake). New treatment to correct these energy defects would be to simultaneously lower plasma free fatty acids and provide an alternative energy source.